Early Childhood Education and Development in Indonesia : An Investment for a Better Life - World Bank (Washington, DC, 2021)
The purpose of this report is to assist the Government of Indonesia to identify priorities for expanding effective and sustainable early childhood services targeted to children in the first six years of life. The report is organized in three sections. The first section explains how expanding services for young children can help to alleviate inequities in human development outcomes. A second section presents the current situation of the early childhood education and development subsector in Indonesia and emerging issues. The final section sets forth recommendations.